2022
DOI: 10.3389/fcvm.2022.967659
|View full text |Cite
|
Sign up to set email alerts
|

Using human induced pluripotent stem cell-derived cardiomyocytes to understand the mechanisms driving cardiomyocyte maturation

Abstract: Cardiovascular diseases are the leading cause of mortality and reduced quality of life globally. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) provide a personalized platform to study inherited heart diseases, drug-induced cardiac toxicity, and cardiac regenerative therapy. However, the immaturity of CMs obtained by current strategies is a major hurdle in utilizing hiPSC-CMs at their fullest potential. Here, the major findings and limitations of current maturation methodologies to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…Curiously, it has been shown in cardiac microtissues that the localisation of Cx43 gap junctions is important for sarcomere organisation [89]. Concomitantly, the TEM images obtained from both DAND5 hiPSC-CMs suggested that the contractile machinery of these CMs is composed of low-density myofibrils and Z-bodies associated with immature CMs rather than more-mature sarcomeric structures with clear Z-disks such as those found in adult CMs [76,91]. Nevertheless, myofibrils in the DAND5-C hiPSC-CM appear to be more uniform and thicker than those displayed by the DAND5-KO hiPSC-CM, evidencing the different phenotype displayed by these DAND5 hiPSC-CM lines.…”
Section: Discussionmentioning
confidence: 97%
“…Curiously, it has been shown in cardiac microtissues that the localisation of Cx43 gap junctions is important for sarcomere organisation [89]. Concomitantly, the TEM images obtained from both DAND5 hiPSC-CMs suggested that the contractile machinery of these CMs is composed of low-density myofibrils and Z-bodies associated with immature CMs rather than more-mature sarcomeric structures with clear Z-disks such as those found in adult CMs [76,91]. Nevertheless, myofibrils in the DAND5-C hiPSC-CM appear to be more uniform and thicker than those displayed by the DAND5-KO hiPSC-CM, evidencing the different phenotype displayed by these DAND5 hiPSC-CM lines.…”
Section: Discussionmentioning
confidence: 97%
“…In the case of loading, the mechanical force deforms proteins in the extracellular matrix, the focal adhesions, the numerous interior mechanosensors, and activation of signaling mediators including ERK1/2, FAK, and PKCƐ [ 28 , 30 32 ]. Instead of NRVMs, hiPS-CMs [ 19 , 33 ] would provide better relevance to the human than use of rodent cells. There are many 3D models that are superior to 2D in terms of cell structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is important to consider when investigating SK currents, which are present in hiPSC-CMs ( Zhao et al, 2018 ), given their spatiotemporal relationship with Ca 2+ sources for activation. To overcome limitations related to hiPSC-CM immaturity, tremendous efforts have gone into maturing hiPSC-CMs to improve their electro-contractile profiles, including long-term culture ( Lundy et al, 2013 ; Lewandowski et al, 2018 ), biophysical modification such as extracellular matrices ( Herron et al, 2016 ; Ogasawara et al, 2017 ) and polydimethylsiloxane (PDMS)-based polymers ( Thavandiran et al, 2013 ) with low tensile strength ( McCain et al, 2014 ; Ribeiro et al, 2015 ), metabolic and hormonal supplementation ( Nakano et al, 2017 ; Parikh et al, 2017 ; Horikoshi et al, 2019 ; Yang et al, 2019 ; Feyen et al, 2020 ), electrical stimulation ( Chan et al, 2013 ), and 3D tissue engineering ( Huethorst et al, 2016 ; Lemoine et al, 2017 ; Correia et al, 2018 ; Ulmer et al, 2018 ; Silbernagel et al, 2020 ), which have been previously reviewed in more detail elsewhere ( Hamledari et al, 2022 ). Importantly, many of these approaches have successfully improved the electro-contractile properties, as shown by: a) increased KCNJ2 expression and I K1 current density along with lower RMP values ( Nunes et al, 2013 ; Herron et al, 2016 ; Abilez et al, 2018 ; Horváth et al, 2018 ; Feyen et al, 2020 ; Huang et al, 2020 ), b) higher expression of SCN5A and upstroke velocity ( Herron et al, 2016 ; Lemoine et al, 2017 ; Feyen et al, 2020 ), c) lower HCN4 expression and I f current density ( Ronaldson-Bouchard et al, 2018 ) with lower intrinsic beating rates, d) greater Ca 2+ handling, storage, and expression of associated proteins (RyR2, SERCA, NCX1, CASQ2) ( Richards et al, 2016 ; Ruan et al, 2016 ; Parikh et al, 2017 ; Shadrin et al, 2017 ; Ronaldson-Bouchard et al, 2018 ; Feyen et al, 2020 ; Huang et al, 2020 ), and e) T-tubule formation and improved sarcomere alignment ( Mills et al, 2017 ; ...…”
Section: Hipsc-cms As a Model For The Study Of Sk Channel Risk Variantsmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org Correia et al, 2018;Ulmer et al, 2018;Silbernagel et al, 2020), which have been previously reviewed in more detail elsewhere (Hamledari et al, 2022). Importantly, many of these approaches have successfully improved the electro-contractile properties, as shown by: a) increased KCNJ2 expression and I K1 current density along with lower RMP values (Nunes et al, 2013;Herron et al, 2016;Abilez et al, 2018;Horváth et al, 2018;Feyen et al, 2020;Huang et al, 2020), b) higher expression of SCN5A and upstroke velocity (Herron et al, 2016;Lemoine et al, 2017;Feyen et al, 2020), c) lower HCN4 expression and I f current density (Ronaldson-Bouchard et al, 2018) with lower intrinsic beating rates, d) greater Ca 2+ handling, storage, and expression of associated proteins (RyR2, SERCA, NCX1, CASQ2) (Richards et al, 2016;Ruan et al, 2016;Parikh et al, 2017;Shadrin et al, 2017;Ronaldson-Bouchard et al, 2018;Feyen et al, 2020;Huang et al, 2020), and e) T-tubule formation and improved sarcomere alignment (Mills et al, 2017;Parikh et al, 2017;Ronaldson-Bouchard et al, 2018;Feyen et al, 2020;Huang et al, 2020).…”
Section: Ion Channel Expression Profiles and Maturationmentioning
confidence: 99%